Answer:
See below.
Step-by-step explanation:
Recall the equation for a circle:
[tex](x-h)^2+(y-k)^2=r^2[/tex], where (h,k) is the center and r is the radius.
We need to turn the given equation into the above format. We do this by completing the square.
First, group them:
[tex](x^2+18x)+(y^2+14y)=-105[/tex]
For the first section, complete the square for [tex]x^2+18x[/tex]:
[tex]x^2+18x+81-81[/tex]
[tex](x+9)^2-81[/tex]
Do the same for the second:
[tex]y^2+14y[/tex]
[tex]y^2+14y+49-49[/tex]
[tex](y+7)^2-49[/tex]
All together:
[tex]((x+9)^2-81)+((y+7)^2-49)=-105[/tex]
[tex](x+9)^2+(y+7)^2-130=-105[/tex]
[tex](x+9)^2+(y+7)^2=25[/tex]
The center is (-9,-7).
The radius is [tex]\sqrt{25}=5[/tex]